The spirit is moving : new pathways in pneumatology : studies presented to Professor Cornelis van der Kooi on the occasion of his retirement - Kooi, Cornelis van der,; Brink, Gijsbert van den, 1963- (Studies in Reformed Theology, 2019)
The work of the Spirit of God is a vibrant and much discussed topic in many contemporary Christian communities worldwide. Apparently, the Spirit is moving. Theological reflection on this phenomenon has even given rise to what is often called a 'pneumatological renaissance'. This volume not only takes stock of these remarkable developments, but also probes some of their hidden aspects and highlights avenues for future exploration. It contains a wide-ranging but coherent assortment of essays, covering the five relations of the Holy Ghost distinguished already in the Nicene-Constantinopolitan Creed: how does the Spirit of God relate to the Bible, to the Christ, to the human person, to the church and to the world? These essays are written as a tribute to the many inspiring theological contributions of prof. Cornelis van der Kooi on the occasion of his retirement as Professor of Systematic Theology at the Faculty of Religion and Theology, Vrije Universiteit Amsterdam, where he taught from 1992 until 2018. Contributors are: Henk A. Bakker, Abraham van de Beek, Erik A. de Boer, Carl J. Bosma, Gijsbert van den Brink, Martien E. Brinkman, Gerard C. den Hertog, Arnold Huijgen, Gerrit C. van de Kamp, Miranda Klaver, Akke van der Kooi, Margriet van der Kooi-Dijkstra, Bruce L. McCormack, Richard J. Mouw, Bert Jan Lietaert Peerbolte, Eveline van Staalduine-Sulman, Eep Talstra, Benno van den Toren, Jan Veenhof, Willem van Vlastuin, Pieter Vos, Michael Welker, Cory Willson, Maarten Wisse.